Operations and supply chain management the core - Jacobs, F. Robert; Chase, Richard B. (The McGraw Hill series in operations and decision sciences, 2023)
"In Operations and Supply Management: The Core, we take students to the center of the business and focus on the core concepts and tools needed to ensure that these processes run smoothly. The goal of this book is to provide you with the essential information that every manager needs to know about operations and supply chain-related activities in a firm. Things have changed dramatically over the last few years. Organization structures are now much flatter, and rather than being functionally organized, companies often are organized by customer and product groups. Today's manager cannot ignore how the real work of the organization is done. This book is all about how to get the real work done effectively. It makes little difference if you are officially in finance, marketing, accounting, or operations: The value-added work, the process of creating and delivering products, needs to be completed in a manner that is both high quality and maximally efficient. Many of the things you do, or will do, in your job are repetitive, even some of the most creative and high-profile activities. You should think of this course as preparing you to be your most productive and helping you help your organization be its most productive"--